2016
DOI: 10.1038/eye.2016.43
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of S100A4, a metastasis-associated protein, inhibits retinal neovascularization via the downregulation of BDNF in oxygen-induced ischaemic retinopathy

Abstract: Background To investigate the underlying mechanism of S100A4 function and whether it has a role in retinal neovascularization (RNV) in a mouse model of oxygen-induced retinopathy (OIR). Methods Retinas from a mouse model of OIR were treated with and without an intravitreous injection of adenoviral-S100A4-RNAi or adenoviral green fluorescence protein (GFP) at postnatal day 12 (P12). At P17, the efficacy of adenoviral gene transfer was assessed using fluorescence microscopy and western blot analysis. RNV was eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 36 publications
1
8
1
Order By: Relevance
“… 11 In addition, retinal neovascularization can be ameliorated by inhibition of S100A4 in an oxygen-induced retinopathy mouse model. 35 , 36 On the basis of those findings, our study put forward a way for corneal repair by targeting S100A4.…”
Section: Discussionmentioning
confidence: 70%
“… 11 In addition, retinal neovascularization can be ameliorated by inhibition of S100A4 in an oxygen-induced retinopathy mouse model. 35 , 36 On the basis of those findings, our study put forward a way for corneal repair by targeting S100A4.…”
Section: Discussionmentioning
confidence: 70%
“…It regulates the expression of S100A4 in fibroblast-regulated intestinal and pulmonary tissue fibrosis [ 51 , 52 ]. Research indicates that S100A4 confers idiopathic pulmonary fibrosis lungs harboring fibrogenic mesenchymal progenitor cells with fibrogenicity [ 53 ]. Hypertrophic scars in tissues, followed by fibrosis induced by TNF-α, lead to an increase in MMP, S100A4, and vimentin expression, which can be antagonized by bone morphogenetic protein 2/4 [ 54 ].…”
Section: Underlying Mechanisms Of S100a4 In Non-tumor Pathophysiologimentioning
confidence: 99%
“…Research has shown that S100A4 is a pro-angiogenic factor that participates in angiogenesis, endothelial cell migration and invasion via its interaction with annexin 2, formation of plasmin, and stimulation of MMP production [ 78 , 79 ]. S100A4-mediated angiogenesis also functions synergistically with the vascular endothelial growth factor, which is an important angiogenic factor that promotes neo-vascularization and vascular leakage through an upstream regulator, the brain-derived growth factor [ 53 , 78 ].…”
Section: Underlying Mechanisms Of S100a4 In Non-tumor Pathophysiologimentioning
confidence: 99%
See 2 more Smart Citations